Analysis of the Impact of Payroll Accounting and Service Charge on the Work Commitment of PT Samaja Bali Villas Employees - I Made Samjaya RAJISTHA; Ni Putu RIASNING; Ni Made Vita INDRIYANI (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This study is entitled